Fabrication of nanoscale core–shell structured lead azide/porous carbon based on a metal–organic framework with high safety performance. (18th February 2022) - Yan, Zhenzhan; Yang, Li; Tong, Wenchao; Han, Ji-Min
Abstract : Carbon-based lead azide with nano-scale lead azide coated with a carbon shell (LA/C) was prepared using a lead-containing MOF material. The prepared LA/C exhibits excellent electrostatic sensitivity (1.84 J), higher LA content (85%), and better ignition ability (22 cm) compared to other reported modified LA materials. Abstract : In this work, we used a lead-containing MOF material as the precursor material to prepare a carbon-based lead azide with nano-scale lead azide coated with a carbon shell (LA/C) through carbonization and azide processes. The lead-containing MOF precursor materials, carbide intermediates, and lead azide/carbon with core–shell structures have all been characterized in detail. The exhaustive characterizations demonstrate that the electrostatic sensitivity of LA/C is reduced to 1.84 J, and the flame sensitivity is increased to 22 cm, thanks to the coating effect and excellent electrical and thermal conductivity of the carbon shell. High-speed photography of the initiation process shows that the initiation process of LA/C is extremely short (less than 1 ms) and LA/C has excellent detonation ability. The properties of LA/C are better than those of previously reported pure LA and most modified LA materials. These findings provide a new perspective for the synthesis of superior performance carbon-based primary explosives with a core–shell structure.